2012
DOI: 10.3109/0142159x.2012.642832
|View full text |Cite
|
Sign up to set email alerts
|

Medical students as teachers at CoSMO, Columbia University's student-run clinic: A pilot study and literature review

Abstract: The practical experiences in clinical teaching that students have at SRCs can supplement classroom-based trainings. Medical schools might revisit their SRCs as places for exposure to clinical teaching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Most research on SRC students' experiences has focused on medical students, [13][14][15][16][17][18] who, these studies have found, value the opportunity to serve patients in an interdisciplinary setting. 17,18 These studies have also shown that volunteering at an SRC improves students' attitudes toward IPC 4,10,15 and working with marginalized patients; 18 it also improves students' understanding of health disparities 15,16 and other HCP roles.…”
Section: Ré Sumémentioning
confidence: 99%
“…Most research on SRC students' experiences has focused on medical students, [13][14][15][16][17][18] who, these studies have found, value the opportunity to serve patients in an interdisciplinary setting. 17,18 These studies have also shown that volunteering at an SRC improves students' attitudes toward IPC 4,10,15 and working with marginalized patients; 18 it also improves students' understanding of health disparities 15,16 and other HCP roles.…”
Section: Ré Sumémentioning
confidence: 99%
“…There are several educational benefits of these community-specific student-run clinics, such as cultural competency, basic clinic skills, and practical clinical teaching experience. 12 …”
Section: Discussionmentioning
confidence: 99%
“…Beyond their future teaching role as residents, undergraduate curricular changes towards student‐directed learning have seen medical students now almost universally involved in peer education . Additionally, a few medical schools have developed elective programmes in which senior medical students adopt a structured teaching role supervising ‘pre‐clinical’ or junior medical students in clinical settings . Despite this expanding peer‐teaching role, there has been limited scholarly investigation of these activities.…”
Section: Introductionmentioning
confidence: 99%
“…6 Additionally, a few medical schools have developed elective programmes in which senior medical students adopt a structured teaching role supervising 'pre-clinical' or junior medical students in clinical settings. 7,8 Despite this expanding peer-teaching role, there has been limited scholarly investigation of these activities. Studies to date have focused primarily on the experience of the student as the teacher.…”
Section: Introductionmentioning
confidence: 99%